2009
DOI: 10.1148/radiol.2523080351
|View full text |Cite
|
Sign up to set email alerts
|

Renal Resistive Index and Long-term Outcome in Chronic Nephropathies

Abstract: An RI of 0.70 or higher is predictive of an unfavorable outcome in patients with chronic nephropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 34 publications
8
92
0
Order By: Relevance
“…Furthermore, even when analysis was restricted to the subgroup with eGFR Ͻ60 mL/min per 1.73 m 2 , which is defined as chronic kidney disease, 24 the independent role of RI in outcomes was maintained. These findings were partially in agreement with those from previous studies on high-risk patients with chronic nephropathy, 6 transplant renal allograft, 22 or heart failure 12 and extend the predictive role of renal hemodynamic abnormalities to essential hypertensive patients. These findings corroborate the hypothesis that the impact of RI on cardiovascular and renal risk is marked and that identifying renal hemodynamic abnormalities is useful for predicting cardiovascular and renal outcomes, especially in hypertensive patients with chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, even when analysis was restricted to the subgroup with eGFR Ͻ60 mL/min per 1.73 m 2 , which is defined as chronic kidney disease, 24 the independent role of RI in outcomes was maintained. These findings were partially in agreement with those from previous studies on high-risk patients with chronic nephropathy, 6 transplant renal allograft, 22 or heart failure 12 and extend the predictive role of renal hemodynamic abnormalities to essential hypertensive patients. These findings corroborate the hypothesis that the impact of RI on cardiovascular and renal risk is marked and that identifying renal hemodynamic abnormalities is useful for predicting cardiovascular and renal outcomes, especially in hypertensive patients with chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 In addition, histological studies demonstrated that RI not only reflects changes in intrarenal perfusion and renovascular resistance but was increased in several pathological conditions, such as renal atherosclerosis 8 and tubulointerstitial damage. 9,10 In previous studies, the prognostic value of RI was examined only in chronic nephropathy, 6 elderly, 11 or heart failure patients…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mild to moderate renal dysfunction, RRI predicts CKD progression and poor outcome especially when RRI C0.7, independently from others measures like eGFR, maybe due to advanced glomerulosclerosis [16][17][18].…”
Section: Rri and Chronic Kidney Disease (Ckd)mentioning
confidence: 96%
“…RI >0.7 was considered pathologic. 3 Weighted kappa was used to evaluate the intra-rater re-liability by the same observer. The kappa values for RI and S/D were 0.975 and 0.965, respectively.…”
Section: Methodsmentioning
confidence: 99%